A prospective, multicenter registry study to evaluate the clinical feasibility of targeted axillary dissection (TAD) in node-positive breast cancer patients - Kümmel, Sherko; Heil, Jörg; Rueland, Anna; Seiberling, Christine; Harrach, Hakima; Schindowski, Dorothea; Lubitz, Juliane; Hellerhoff, Karin; Ankel, Christine; Graßhoff, Sven-Thomas; Deuschle, Petra; Hanf, Volker; et al. (Annals of surgery, 2022)
This study aimed to investigate the feasibility and accuracy of non-radioactive TLN biopsy and TAD in routine clinical practice.
Online veröffentlicht am 4. November 2020
Gesehen am 03.01.2023